Transcriptional profiles analysis of effects of Toxoplasma gondii rhoptry protein 16 on THP-1 macrophages - Yang, Ningai; Li, Mingyang; Yang, Hong; Li, Jiaming; Dang, Tiantian; Li, Guangqi; Zhao, Zhijun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionToxoplasma gondii, an intracellular parasitic protozoan, is globally recognized for its ability to cause parasitic diseases and has developed diverse strategies to evade immune-mediated elimination. The protein ROP16 of T.gondii plays a crucial role in this evasion process by specifically targeting macrophages and mononuclear phagocytes in vivo. However, the precise mechanisms underlying the involvement of type II ROP16 proteins in infection, inflammation, and other processes remain unknown.MethodsTo investigate the mechanism of action of gonococcal ROP16 proteins in human macrophages, we constructed a lentivirus overexpressing ROP16 and established stably transfected cell lines. We then analyzed the gene transcriptional profiles of ROP16 II in THP-1 macrophages using transcriptome sequencing. Interaction networks were constructed by screening differentially expressed genes and performing gene function enrichment analysis.ResultsAs a result, five differentially expressed genes were identified: AAMDC, GPR158, RAD9A, STOML1, and STRA13. Immuno-featured differential analysis showed that type 17 T helper cells were more strongly correlated with GPR158 and STRA13, while CD8 T-cell was most strongly correlated with STOML1.DiscussionTherefore, we conclude that the ROP16 protein plays a pivotal role in THP-1 macrophage infection and these five differentially expressed genes may serve as promising molecular targets for the prevention or control of toxoplasmosis. These findings have significant implications for the diagnosis and treatment of toxoplasmosis.